Environmental Engineering: Review for the Professional Engineering Examination - Naimpally, Ashok V. (Springer US : Imprint: Springer, 2013)
Summarizes the theoretical background of topics covered in the Principles and Practice of Engineering Examination in the area of Environmental Engineering. Includes two practice exams with 100 problems each, and solutions to each problem are provided. Each problem includes answers that result from common mistakes, which helps readers to quickly build a solid foundation in the subject. This review will help candidates prepare for the Principles and Practice of Engineering Examination in the area of Environmental Engineering by refreshing their memory of key concepts and theory. In addition to a review of theory, two practice exams following the multiple choice format used by the PE exam are supplied with solutions to every problem. The material covered in the book and tested in the practice exam includes: Water resources, distribution, and treatment Waste water collection and treatment Groundwater resources, soils, and remediation Air pollution transport and treatment Solid waste disposal, treatment, and recycling Hazardous waste minimization, treatment, and disposal Environmental assessments and emergency response Errors and uncertainty in environmental measurements.